Efeito da desproteinização no grau de conversão e na resistência de união de cimentos resinosos autoadesivos à dentina - Rodrigues, Nara Sousa (2016)
The adhesive resin cements not completely dissolve the smear layer and the resulting surface interaction that occurs between cement and dentin can be harmful. Sodium hypochlorite (NaOCl) may cause the removal of collagen, with an option to eliminate this mechanical barrier, which may enhance the chemical interaction between cement and dentine. This study evaluated the effect of two deproteinization strategies in bond strength to dentin (UK), degree of in situ conversion (GC) and nanoleakage (NI) two self-adhesive resin cements after 24 h and after 200,000 mechanical cycles. One hundred and fourteen human third molars were divided into six groups according to cement used and deproteinization strategy: RelyX U200 (UK) following the manufacturer's instructions (control), RU after the deproteinization in the mineralized dentin using sodium hypochlorite (RU - NaOCl), RU after etching (15 sec) and deproteinized dentin (RU - Etching + NaOCl) Maxcem Elite (ME) following the manufacturer's instructions (control), ME after deproteinization dentin (ME - NaOCl) ME after etching (15 sec) and deproteinized dentin (ME - Etching + NaOCl). The specimens were randomly divided into two subgroups for the microtensile test: tested in the immediate period and after 200,000 mechanical cycles. For NI, two slices of each group were infiltrated with ammoniacal silver nitrate solution prepared and analyzed by SEM. GC-situ three specimens of each group was immediately measured in micro-Raman spectroscopy. Data were statistically analyzed by ANOVA two criteria and multiple comparisons Tukey test (p <0.05). The deproteinization of dentine without acid etching increased the RU values ​​of the two cements in immediate groups. The dentine deproteinization decreased the GC for both cements. After the mechanical cycling, this technique was effective for ME, but did not affect the UK bond strength. The experimental group showed less NI after aging. The long-term benefits of deproteinization presented in this work are encouraging and may justify this additional clinical step.